What comes my way [large type] - Peterson, Tracie (Peterson, Tracie. Brookstone brides, 2019)
Ella Fleming is on the run from her past and the secrets that could tear her family apart. As a member of the Brookstone Wild West Extravaganza, a wild west show comprised of all-female performers, her uncanny talent for trick riding impresses the viewers. Only while performing can she forget the truth about who she really is--the daughter of a murderer. Phillip DeShazer blames himself for his father's death and has done his best to bury his guilt in work and drink. Realizing he needs something more, he seeks answers and finds support and kindness from the beautiful Ella Fleming. However, the more she comes to his rescue, the more his guilt grows. He's fallen in love with her and feels confident that she returns his feelings, but until he can overcome the past and let God guide his future, Phillip knows he's not worthy of Ella's love. Uncertain of what will come their way, Ella and Phillip must learn to trust God even when the road they travel takes them in different directions. Only then can love be a part of their journey.